Mathematical modelling of mass transfer phenomena for sucrose and lactitol molecules during osmotic dehydration of cherries - Maldonado, Mariela Beatriz (2022)
The diffusion phenomena of sucrose and lactitol in cherries using different proportions during osmotic dehydration was quantified by means of a mathematical model based on Fick's second law. The average effective diffusion coefficient for soluble solids in skin and flesh are 5.37 10−11 m2∕s and 1.24 10−10 m2∕s. Whereas, for water in skin and flesh are 9.27 10−09 m2∕s and 5.48 10−08 m2∕s. A significant difference for water diffusion coefficients (p < 0.05) was observed between the treatments. This could indicate that the diffusion between species and treatments is differential. Effective diffusion coefficients for water in skin and flesh are 2 orders of magnitude greater than effective diffusion coefficients for soluble solids. This is probably due to its lesser molecular weight. Furthermore, the effective diffusion coefficients for water and soluble solids in cherry skin are between 1 and 2 orders of magnitude lower than effective diffusion coefficients for both in cherry flesh, possibly due to the barrier effect exerted by the cherry skin.